Perbandingan Hukum Keluarga di Indonesia dan Aljazair Tentang Nafkah - Sari, Septi Wulan (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to compare family law in Indonesia and Algeria about living both in its similarities and differences, especially in the legal basis and its use. This research was made using library research which in its work by collecting book sources, journals, and internet sources. The results showed that the legal basis for living in Indonesia concerning the Rights and Obligations of husband and wife is regulated in Law No. 16 of 2019 concerning Marriage Articles 30 to 34, as well as in the Compilation of Islamic Law Chapter XII Pasa 77 to 84. Meanwhile, in the country of Algeria, it is regulated in the Family Law Code (Ordinance Marriage) Article 37. In Islamic law, the Algerian state is more dominantly inclined to the maliki school, se to the regulation of marriage and also the dominant living following the Maliki mahzab, in contrast to the Indonesian state the majority of the followers of the Shafi'i mahzab. The similarities between the two countries about living are seen in the rate of giving that does not look at social status. However, for the Algerian country, nafjah is only required to have primary materials, while in Indonesia it must be in the form of primary, tertiary, and secondary needs.